The Effect of Profitability, Leverage, and Size on Environmental Disclosure with the Proportion of Independent Commissioners as Moderating - Ardi, Jalu Wicaksono; Yulianto, Agung (Accounting Analysis Journal, 2020)
The purpose of this study is to evaluate the effect of profitability, leverage, and company size on environmental disclosure with the proportion of independent directors as moderator. A maximum of 61 agricultural and mining sector companies listed on the Indonesia Stock Exchange in 2014-2018 was the population of this report. The sampling method used purposing sampling, so with 45 units of analysis, we get 9 sample companies. The quantitative method used regression analysis for balance. The results show that profitability does not influence on environmental disclosure. Leverage has a negative effect on environmental disclosure. Company size has a positive effect on environmental disclosure. The proportion of independent directors is able to moderate the effect of profitability on environmental disclosure but is not able to moderate the effect of leverage and company size on environmental disclosure. This study concludes that leverage has a negative relationship with environmental disclosure and firm size has a positive relationship with environmental disclosure and the proportion of independent commissioners moderates the relationship between profitability and environmental disclosure. The findings show the important role of independent commissioners in environmental disclosure, namely providing investors with a balance and maintaining an unbiased and impartial atmosphere.